Sharing responsibility with a machine - Oliver Kirchkamp; Christina Strobel (Friedrich Schiller University Jena, 2018)
Humans make decisions jointly with others. They share responsibility for the outcome with their interaction partners. Today, more and more often the partner in a decision is not another human but, instead, a machine. Here we ask whether the type of the partner, machine or human, affects our responsibility, our perception of the choice and the choice itself. As a workhorse we use a modified dictator game with two joint decision makers: either two humans or one human and one machine. We find no treatment effect on perceived responsibility or guilt. We also find only a small and insignificant effect on actual choices.
Keywords: C91; D63; D80; 330; Human-computer interaction; Experiment; Shared responsibility; Moral wiggle room